The impact of a quality management program for patients undergoing head and neck resection with free-flap reconstruction: longitudinal study examining sustainability - Joseph C. Dort; Khara M. Sauro; Shamir Chandarana; Christiaan Schrag; Jennifer Matthews; Steven Nakoneshny; Vida Manoloto; Tanya Miller; C. David McKenzie; Robert D. Hart; T. Wayne Matthews (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Care pathways (CPs) are helpful in reducing unwanted variation in clinical care. Most studies of CPs show they improve clinical outcomes but there is little known about the long-term impact of CPs as part of a sustained quality management program. Head and neck (HN) surgery with free flap reconstruction is complex, time-consuming and expensive. Complications are common and therefore CPs applied to this patient population are the focus of this paper. In this paper we report outcomes from a 9 year experience designing and using CPs in the management of patients undergoing major head and neck resection with free flap reconstruction. Methods The Calgary quality management program and CP design is described the accompanying article. Data from CP managed patients undergoing major HN surgery were prospectively collected and compared to a baseline cohort of patients managed with standard care. Data were retrospectively analyzed and intergroup comparisons were made. Results Mobilization, decannulation time and hospital length of stay were significantly improved in pathway-managed patients (p = 0.001). Trend analysis showed sustained improvement in key performance indicators including complications. Return to the OR, primarily to assess a compromised flap, is increasing. Conclusions Care pathways when deployed as part of an ongoing quality management program are associated with improved clinical outcomes in this complex group of patients.